Self-Control as a Mediating Between Fintech Loans, Financial Literacy, and Gen Z's Lifestyle in Semarang - C. Tri Widiastuti,; Oktavia Rian Ramadani,; Rahma Indah Kusumaningrum, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aimed to investigate the role of self-control in mediating the impact of financial technology on Generation Z through online loans, financial literacy, and lifestyle. Quantitative techniques were applied, with Generation Z in Semarang as the research population. The sampling method used was convenience sampling, totaling 192 respondents. Data were collected using a Likert scale questionnaire and analyzed with Smart PLS 3.0. The analysis used the Outer Model (Measurement Model) to evaluate Convergent Validity, Discriminant Validity, and Composite Reliability, and the Inner Model to calculate R-Square and conduct a t-test. Hypothesis testing was performed through bootstrapping, which involved resampling from the original sample. The findings indicate that financial technology, namely online loans, has a good and significant impact on self-control and lifestyle. Likewise, financial knowledge improves self-control and lifestyle. Furthermore, self-control significantly impacts lifestyle and may act as a mediator between financial technology, financial literacy, and lifestyle. The findings of this study underscore the need for higher education to strengthen Gen Z's financial literacy to raise awareness of the need for wise financial management in ensuring economic resilience and stability.